2013
DOI: 10.1159/000350525
|View full text |Cite
|
Sign up to set email alerts
|

Update on Body Composition and Bone Density in Children with Prader-Willi Syndrome

Abstract: Aim: To compare body composition in children with Prader-Willi syndrome (PWS) not naïve to growth hormone (GH) with obese and lean controls. Methods: Participants included 12 children with PWS, 12 children with obesity (body fat percentage >95th percentile for age and sex) and 12 lean children (body fat percentage <85th percentile for age and sex) matched by age and height. Fat mass, lean mass, bone mineral content (BMC), bone mineral density (BMD) and BMD z-score for total body, hips and lumbar spine were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…GH treatment has been shown to significantly improve BMD [21]. Sex hormone replacement unexpectedly appears to have no effect on bone mineral density in one study [20], however, Longi et al [22] showed that bone strength was lower in adult PWS patients who were treated with sex steroids but did not receive GH replacement [22].…”
Section: Discussionmentioning
confidence: 99%
“…GH treatment has been shown to significantly improve BMD [21]. Sex hormone replacement unexpectedly appears to have no effect on bone mineral density in one study [20], however, Longi et al [22] showed that bone strength was lower in adult PWS patients who were treated with sex steroids but did not receive GH replacement [22].…”
Section: Discussionmentioning
confidence: 99%
“…49 In children, the bone mineral content is also reduced when compared with children with similar BMI. Rubin et al 50 compared the body composition of twelve children (8-11 years) with PWS who were not GH-naïve with that of obese and lean controls. The authors studied BMC, BMD, and the BMD z score for the patient's total body, hips, and lumbar spine.…”
Section: Osteoporosis and Bone Densitymentioning
confidence: 99%
“…The authors found significantly lower BMC and BMD in those with PWS compared to obese controls, but there were no differences between PWS and lean controls. 50 At the moment, there are no protocols for the prevention of osteoporosis in adolescents or adults with PWS, although with the use of rhGH from an early age and the improvement in muscular tone and physical activity, the body composition of these patients may improve not only by reducing the weight gain, but also by increasing their bone mass.…”
Section: Osteoporosis and Bone Densitymentioning
confidence: 99%
“…If energy intake and expenditure are not tightly regulated, the syndrome can result in morbid obesity. Individuals with PWS exhibit high adiposity and a lower lean mass and daily energy expenditure when compared to equally obese controls [2, 3]. Common endocrine abnormalities include growth hormone (GH) deficiency and hypogonadism [4].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, recommendations have been made for children to engage in muscle- and bone-strengthening exercises at least twice a week [11]. Because of the inherent characteristics of poor lean mass and bone mineral density [3], increased fracture risk [12], and overall low energy metabolism in PWS [2], RE is recommended as part of the exercise regimen for individuals with PWS [7]. Moreover, preliminary studies have demonstrated improvements in muscle strength with exercise in PWS [7].…”
Section: Introductionmentioning
confidence: 99%